High Capacity Sulfurized Alcohol Composite Positive Electrode Materials Applicable for Lithium Sulfur Batteries. Issue 1 (30th December 2016) - Takeuchi, Tomonari; Kojima, Toshikatsu; Kageyama, Hiroyuki; Mitsuhara, Kei; Ogawa, Masahiro; Yamanaka, Keisuke; Ohta, Toshiaki; Kobayashi, Hironori; Nagai, Ryo; Ohta, Akira
Abstract : New sulfur-carbon composite positive electrode materials were synthesized through sulfurizing primary alcohols, and their electrochemical properties were examined. The sulfurized alcohol composites (SACs) showed relatively higher sulfur contents (more than 60 wt%) and were revealed to be an amorphous structure by high-resolution TEM observations. Raman and XAFS spectra showed the presence of S – S, C – S, and C – C bonds, and the C – C bonds mainly consisted of sp 3 components, which makes a clear contrast to the previously reported organosulfur materials where the C – C bonds mainly consisted of sp 2 components. The SAC positive electrode cells showed discharge capacities of more than 900 mAh·g −1 with relatively reduced cycle degradation.